2018
DOI: 10.3390/biology7040046
|View full text |Cite
|
Sign up to set email alerts
|

Selectable Markers and Reporter Genes for Engineering the Chloroplast of Chlamydomonas reinhardtii

Abstract: Chlamydomonas reinhardtii is a model alga of increasing interest as a cell factory for the production of valuable compounds, including therapeutic proteins and bioactive metabolites. Expression of foreign genes in the chloroplast is particularly advantageous as: (i) accumulation of product in this sub-cellular compartment minimises potential toxicity to the rest of the cell; (ii) genes can integrate at specific loci of the chloroplast genome (plastome) by homologous recombination; (iii) the high ploidy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 137 publications
0
46
0
Order By: Relevance
“…We have also demonstrated that our ptxD cassette can serve as a dominant selectable marker for chloroplast transformation and have constructed suitable plasmids for targeting the cassette into a neutral site on the plastome (either at the psbH-trnE2 or the psaA-3-trnL locus). Sandoval-Vargas et al (2019) have also recently reported the use of ptxD as a selectable marker for the C. reinhardtii chloroplast, and our combined work adds a useful dominant marker to the molecular toolbox (Esland et al 2018). Importantly, this marker is not derived from a bacterial antibiotic resistance gene and therefore raises less concerns regarding GM regulation (EFSA GMO Panel 2004;Beacham et al 2017).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We have also demonstrated that our ptxD cassette can serve as a dominant selectable marker for chloroplast transformation and have constructed suitable plasmids for targeting the cassette into a neutral site on the plastome (either at the psbH-trnE2 or the psaA-3-trnL locus). Sandoval-Vargas et al (2019) have also recently reported the use of ptxD as a selectable marker for the C. reinhardtii chloroplast, and our combined work adds a useful dominant marker to the molecular toolbox (Esland et al 2018). Importantly, this marker is not derived from a bacterial antibiotic resistance gene and therefore raises less concerns regarding GM regulation (EFSA GMO Panel 2004;Beacham et al 2017).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the ability to metabolise Phi to Pi is very unlikely to arise spontaneously in the recipient cell so false positives are unlikely during transformation. Given that there is a dearth of selectable markers for engineering the algal chloroplast (Day and Goldschmidt-Clermont 2011;Esland et al 2018), we tested whether transformation of C. reinhardtii using pWUCA2-ptxD could be achieved by direct selection on Tris-acetate medium containing 1 mM Phi as the only source of phosphorus. As an initial test, we used the negative control strain (TN72 transformed to phototrophy using pWUCA2) as a recipient line, as illustrated in Fig.…”
Section: Ptxd As a Non-antibiotic Selectable Marker For Chloroplast Tmentioning
confidence: 99%
“…Gene knockdown by introduction of antisense, artificial small RNAs, and CRISPRi has been implemented in multiple systems (De Riso et al, 2009;Zhao et al, 2009;Yao et al, 2016;Wei et al, 2017;Sun et al, 2018). Site-specific genetic manipulation by homologous recombination (HR) is routine in cyanobacteria (Zang et al, 2007), the chloroplast genome of C. reinhardtii (Esland et al, 2018), and the nuclear genome of Nannochloropsis (Kilian et al, 2011). In contrast, HR occurs at a low frequency in the nuclear genome of C. reinhardtii and P. tricornutum, but can be induced in the presence of doublestrand DNA breaks by targeted endonucleases, enabling targeted gene knockout and/or knock-in (Shin et al, 2016;Greiner et al, 2017;Kroth et al, 2018).…”
Section: Synthetic Biologymentioning
confidence: 99%
“…These include a wide range of therapeutic proteins such as vaccines, hormones and antibodies [11]; industrial enzymes [15,16], and enzymes for synthesizing novel metabolites in the organelle [17][18][19][20][21]. However, in almost all cases the genetic engineering has involved the insertion of just one transgene (or a single transgene together with a bacterial gene such as aadA or aphA-6 as the selectable marker [13]). In the few remaining reports, two transgenes have been employed -either as a dicistronic operon [22]; as two linked gene cassettes inserted into Fig.…”
mentioning
confidence: 99%
“…This gene encodes a subunit of the dark-operative protochlorophyllide reductase and a knockout of chlL gives rise to a 'yellow-in-the-dark' phenotype [36]. Consequently, the insertion of transgenes into chlL can be used as a simple screen to distinguish genuine aadA transformants from spectinomycin-resistant clones arising from spontaneous mutation [13].…”
mentioning
confidence: 99%